Mobile Toolbox: Age‐related change on remote, smartphone‐based measures of cognition. (20th December 2022) - Nowinski, Cindy J.; Kaat, Aaron J.; Slotkin, Jerry; La Forte, Erica M; Shono, Yusuke; Novack, Miriam; Pila, Sarah; Amagai, Saki; Hosseinian, Zahra; Adam, Hubert; Gershon, Richard C.
Abstract: Background: Differentiating normal from pathological cognitive change in adults is essential for both preventing and treating abnormal cognitive decline. The Mobile Toolbox (MTB) is an app‐based research platform and expandable test library enabling remote assessment of cognition using participants' own smartphones (iOS and Android). MTB facilitates conduct of diverse types of cognitive research with a broad range of participants, including those who may be hard to reach. However, evidence for MTB test validity, including demonstration of expected age‐related changes in adulthood, is needed to support MTB use. We present findings on associations between age and MTB performance. Method: 1, 120 English‐speaking participants, ages 18–90, were recruited by a market research company as part of a larger study. Participants completed MTB remote measures of executive function, episodic and working memory, processing speed, and language on their smartphones. Measure order was fixed ((Vocabulary, Memory for Sequences, Spelling, Picture Sequence Memory (PSM), Flanker, Face Name (FNAME) Learning, Dimensional Change Card Sort (DCCS), Number Match, Face Name Memory)); individual tests could be taken anytime within a 14‐day period. Spearman correlation coefficients were calculated to evaluate relationships between age and test scores. Result: Our participant sample was 57% female, 13% Hispanic, 72% white; mean age = 45 (sd = 21). Education distribution was: < high school (2%); high school (34%); some college (34%), college (20%), graduate degree (11%). Measures of executive function (DCCS and Flanker: r = ‐0.50; ‐0.57) and processing speed ( r = ‐0.56) showed decreased performance with age (all p < 0.001). Episodic memory scores also decreased with age, but correlations were weaker (PSM and FNAME: ‐0.2, ‐0.35; p.<.001). Performance on language tests did not significantly decrease with age. Conclusion: Most MTB measures correlated with age in the expected directions. Fluid cognition (e.g., executive function and processing speed) and memory typically decrease with age, and this decrease was reflected in MTB test performance. In contrast, crystallized abilities (e.g., spelling and vocabulary), which are typically preserved as we age, did not decrease in our sample. Initial results suggest MTB can be used to identify abnormal cognitive decline and support its use in cognitive aging research.